Examining Postoperative Posterior Cruciate Ligament Index: A Structural Paradigm in Anterior Cruciate Ligament (ACL) Reconstructions With Hamstring Tendon Autograft - Yalin, Mustafa; Key, Sefa; Yildirim, Mustafa; Agar, Anil (Springernature, 2024)
Background: The current study aimed to compare the posterior cruciate ligament (PCL) index values of patients who underwent hamstring tendon (HT) autograft reconstruction due to an anterior cruciate ligament (ACL) tear. The comparison involved assessing these values in a similar cohort and evaluating the association between the alteration in the PCL index and functional results. Methods: Patients who were clinically diagnosed with a complete, unilateral ACL tear and underwent ACL reconstruction (ACLR) using HT autograft between January 2018 and January 2021 constituted the operated group (Group 1) of the study. The control group (Group 2) consisted of patients selected from a convenience sample without ACL rupture, meniscal lesion, or cartilage damage who underwent an MRI during an outpatient orthopaedic consultation for knee pain. The operated group was submitted for an MRI of the knee one year after the operation for any reason such as pain, graft healing, the presence of tunnel widening, or suspicion of re -rupture. The International Knee Documentation Committee (IKDC) Subjective Knee Evaluation Form and the Lysholm Scoring System were applied to the patients in the operated group in the preoperative and postoperative periods to evaluate their complaints, function, and participation in sports and to assess functional ability and functional capacity. A radiologist with five years of experience measured the PCL index in the sagittal section of an MRI. In the operated group, changes in PCL index, IKDC, and Lysholm values during the postoperative period were assessed, along with their correlation. Additionally, a comparison was made between the values of the operated group and the non -operated group. Results: No statistically significant correlation was found between the PCL index alteration and the functional score alteration (IKDC and Lysholm) in the operated group (p>0.05). In comparison to the nonoperated group, the preoperative PCL index measures of the operated group were significantly lower (p: 0.000; p<0.05). The increase in the postoperative PCL index measurements of the operated group was similarly statistically significant (p: 0.000; p<0.05). Conclusion: Although the PCL index appears to be a strong anatomical structural parameter in ACLR patients performing HT autograft in the postoperative period, its correlation with functional results is weak.
Keywords: arthroscopy; knee; posterior cruciate ligament index; hamstring tendon; anterior cruciate ligament reconstruction